PENGARUH TEMPERATUR ANNEALING TERHADAP SIFAT FISIS BATU BATA LIMBAH SERAT ALAMI - CHANDRA, ARTHA NESA; Djamas, Djusmaini; Ramli, Ramli (Sainstek : Jurnal Sains dan Teknologi, 2016)
This study aims to determine at what temperature annealing which will produce compressive strength and good porosity in the brick waste natural fiber. This study was an experimental study with dick variables such as the proportion of clay and waste of natural powder that is 90%: 10%, each grain size 0.18 mm material, waste natural powder used is sawdust sawmill. The independent variable is the temperature annealing while the dependent variable is the compressive strength and porosity. And wastes natural clay powder mixed and given 5 liters of water, then in print square shaped measuring 6x6x6 cm by 20 pieces to determine the compressive strength and the cylinder-shaped measuring 10 x 7 cm by 4 units to determine the value of porosity. Each of these samples with variations in-Anneal Annealing temperature 7000C, 7500C, 8000C and 8500C using Electric Furnace. After data collection and data analysis of compressive strength and porosity of the importance of the value of the maximum compressive strength of 89.5 kg / cm2 at a temperature of 8500C and this value meets the standards. While the minimum porosity value was 2.10% at the temperature of 8500C.